Factors affecting attitude of medical students to pursue surgical career (Journal of Kathmandu Medical College, 2017)
Background: Medical students are always in a dilemma for their career choice after under-graduation as there are multiple options and none of the choices come without any drawbacks. Multiple factors determine their preferences.Objective: This study aimed to identify the factors that determine career choice and to discuss how it affects the students in taking surgery as their career.Methods: A questionnaire was developed which included factors that encourage and also influence students to consider surgery as their career. A cross-sectional study was conducted among 292 participants and they were divided into two groups, preclinical and clinical students. The collected data was tabulated and analyzed using Statistical Package for Social Sciences version 20.Results: Out of the 292 students, 144 (49.32%) were males and 148 (50.68%) were females. Of the total, 233 (79.8%) students thought of choosing surgery as their career while 41 (14.04%) of the students disagreed for choosing surgery. Among the 233 students, 76 (32.6%) were from preclinical and 157 (67.38%) were clinical students. Better earning and role model influenced them to take surgery as their career whereas lack of private life and great dedication were the deterrent factors.Conclusion: There are various factors that affect students’ preference in opting for surgical career. Even though this study reveals many factors contributing towards one’s interest in surgical field, it was not statistically significant, and hence, the conclusive results could not be drawn.Journal of Kathmandu Medical CollegeVol. 5, No. 3, Issue 17, Jul.-Sep., 2016, page: 85-88